Nutrigenomics Coupling with other OMICS Platform Enhance Personalized Health Care in Metabolic Disorders - Sylvester Ndimele; Miranda L. Carpenter; Jae-Hyeon Cho; Hong Duck Kim (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
Diabetes is a multifactorial of diseases characterized by high blood glucose levels which occur as a result in the body's inability to produce and/or use insulin. Both type 1 and 2 diabetes are thought to be complex disease which developed by the influence of many susceptibility and protective genes, in relation with negative and positive environmental factors. Though type 1 diabetes is distinguished by common beta-cell loss which is mediated by an autoimmune process to extent that all patients with overt type 1 diabetes will essentially need insulin. Multiple genetic factors have been connected to type 1 diabetes which can define individualized plan for type 1 prevention. This review has focused on type 2 diabetes (T2D) which has become more and more a challenging health burden as a result of its degree of morbidity, mortality and heightened prevalence worldwide.